P-selectin levels in women with endometriosis and non-endometriosis - Tonny Simarmata (Universitas Muhammadiyah Surabaya, 2017)
The discovery of a decline in the cellular immune system in endometrial tissue of women with endometriosis triggers the idea that immunologic factors may play a role in the process of endometriosis. This study was conducted to determine differences in blood plasma P-selectin levels in women with endometriosis and non endometriosis. This cross-sectional study was conducted at the Department of Obstetrics and Gynecology of the Faculty of Medicine, University of North Sumatra (FK USU) from April to August 2014. P-selectin levels were measured through blood plasma of women with endometriosis (cases) and non-endometriosis (control) ELISA. Diagnosis of endometriosis is confirmed by histopathologic examination with hematoxylin eosin staining. Statistical tests were performed with t-test and anova. Each of 28 cases of endometriosis and control with age 30-39 years (endometriosis 42.9% and control 57.1%). The endometriosis group is entirely with 0 (100%) parity, while the control with parity is ≥3 (92.9%). Most cases of endometriosis in stage 4 (46.4%). P-selectin levels in endometriosis were clinically higher when compared with non endometriosis (30.89 ± 8.27 vs. 28.36 ± 7.78 ng / ml), but no statistically significant difference was found (p> 0.05). There was an average difference of P-selectin levels based on endometriosis stage but statistically no significant difference was found (p> 0.05). P-selectin levels in endometriosis were clinically higher when compared with non-endometriosis but there was no statistically significant difference.